Histological Validation of FDG and PSMA-Targeted PET/CT Imaging in a Rare Tracheal Adenoid Cystic Carcinoma. (11th January 2023) - Sandach, Patrick; Seifert, Robert; Slama, Alexis; Theegarten, Dirk; Hautzel, Hubertus
Abstract: Adenoid cystic carcinomas are the second most common entity of tracheal malignancies, which have an overall incidence as low as only 0.2 in 100, 000 persons per year. We present the case of a 64-year-old man with a histologically confirmed adenoid cystic carcinoma who sequentially underwent 18 F-FDG PET/CT and 68 Ga-PSMA-11 PET/CT within 1 day for staging 3 days before surgical resection of the tumor. Immunohistochemistry revealed PSMA expression of the tumor corroborating the PSMA PET findings.